Synthesis of Nano/Microsized MIL-101Cr Through Combination of Microwave Heating and Emulsion Technology for Mixed-Matrix Membranes - Gruber, Irina; Nuhnen, Alexander; Lerch, Arne; Nießing, Sandra; Klopotowski, Maximilian; Herbst, Annika; Karg, Matthias; Janiak, Christoph (Frontiers in Chemistry, 2019)
Nano/microsized MIL 101Cr was synthesized by microwave heating of emulsions for the use as a composite with Matrimid mixed-matrix membranes (MMM) to enhance the performance of a mixed-gas-separation. As an example we chose CO2/CH4 separation. Although the incorporation of MIL 101Cr in MMMs is well known, the impact of nanosized MIL 101Cr in MMMs is new and shows an improvement compared to microsized MIL 101Cr under the same conditions and mixed gas permeation. In order to reproducibly obtain nanoMIL 101Cr microwave heating was supplemented by carrying out the reaction of chromium nitrate and 1,4-benzenedicarboxylic acid in heptane in water emulsions with the anionic surfactant sodium oleate as emulsifier. The use of this emulsion with the phase inversion temperature (PIT) method offered controlled nucleation and growth of nanoMIL-101 particles to an average size of less than 100 nm within 70 min offering high apparent BET surface areas (2900 m2 g-1) and yields of 45 %. Concerning the CO2/CH4 separation, the best result was obtained with 24 wt% of nanoMIL 101Cr@Matrimid, leading to 32 Barrer in CO2 permeability compared to 6 Barrer for the neat Matrimid polymer membrane and 21 Barrer for the maximum possible 20 wt% of microMIL 101Cr@Matrimid. The nanosized filler allowed reaching a higher loading where the permeability significantly increased above the predictions from Maxwell and free-fractional-volume modelling. These improvements for MMMs based on nanosized MIL 101Cr are promising for other gas separations.